Digital surface scanning in flap perfusion. Issue 1 (January 2021) - Deferm, J.T.; Baan, F.; Schreurs, R.; Willaert, R.; Maal, T.; Meijer, G.
Abstract: Monitoring vascular perfusion of transferred tissue is essential in reconstructive surgery to recognize early flap failure. The aim of this study was to evaluate the ability of a digital surface scanner to detect vascular perfusion disorders through the monitoring of skin colour changes. A total of 160 surface scans of the forearm skin were performed with a TRIOS 3D scanner. Vascular compromise was simulated at different time-points by intermittent occlusion of the blood supply to the forearm skin (first the arterial blood supply and then the venous blood supply). Skin colour changes were examined according to the hue, saturation, and value colour scale. Colour differences were analysed with a paired t -test. Significant differences were observed between the colour of the normal skin and that of the vascular compromised skin ( P < 0.01). The surface scanner could distinguish between arterial occlusion and venous congestion ( P < 0.01). A digital surface scan is an objective, non-invasive tool to detect early vascular perfusion disorders of the skin.